Analisis Yuridis Terhadap Pencemaran dan Perusakan Lingkungan oleh PT Freeport Indonesia Berdasarkan Ketentuan Hukum Lingkungan Internasional dan Implementasinya di Indonesia - Nova, Sri Asih Roza (Nagari Law Review, 2025)
PT Freeport Indonesia is a mining company based in Indonesia and has been operating in the country for decades. However, since operating in the Papua region, PT Freeport Indonesia has not managed the environment properly. The mining activities are carried out below environmental standards, even very unfeasible so that they cause damage to the local ecology. Its waste that contains B3 (Hazardous and Toxic Substances) has entered areas that function as a source of livelihood for the local community. Therefore, in this scientific article, it analyzes whether the environmental damage carried out by PT Freeport has violated the provisions of international and national environmental laws and analyzes whether the case of pollution and environmental damage by PT Freeport Indonesia can be sued by way of Class Action. The purpose of this writing is to find out and analyze the provisions of international environmental law and their implementation in Indonesia that can be used as a legal basis to sue PT Freeport Indonesia for environmental damage caused by its activities and to find out and analyze whether the case of environmental pollution by PT Freeport Indonesia can be sued by way of Class Action. And from the results of the study, it is known that there are several national international provisions that can be used as a legal basis to sue PT Freeport Indonesia for its environmental pollution activities, namely the Marine Pollution Convention (MARPOL) 1973/1978, the United Nations Convention on the Law of the Sea (UNCLOS) 1982, the 1989 Basel Convention, and the United Nations Framework Convention on Climate Change (UNFCCC) 1992. Nationally, it is regulated by Law Number 32 of 2009 concerning Environmental Protection and Management, as well as Law Number 4 of 2009 concerning Mineral and Coal Mining. Regarding the use of the Class Action system in the lawsuit, it should be used against environmental pollution cases by PT Freeport Indonesia because the impact of the losses caused has involved all tribes and communities around the mining and also to save lawsuit costs.